2018
DOI: 10.1002/cncr.31737
|View full text |Cite
|
Sign up to set email alerts
|

Place of death for patients with cancer in the United States, 1999 through 2015: Racial, age, and geographic disparities

Abstract: BACKGROUND Place of death is an essential component of high quality cancer care and comprehensive national trends and disparities in place of death are unknown. METHODS Deidentified death certificate data were obtained via the National Center for Health Statistics. All cancer deaths from 1999 through 2015 were included. Multivariate logistic regression was used to test for disparities in place of death associated with sociodemographic variables. RESULTS From 1999 through 2015, a total of 9,646,498 cancer death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 61 publications
3
43
0
Order By: Relevance
“…We also observed an increase in the proportion of African Americans dying in the hospital over time, which is consistent with other studies of African American patients with malignancy that have higher shown likelihood of dying in acute care setting [11][12][13]. We would however draw caution in interpreting this finding as inferences on race from the National Inpatient Sample is problematic due to a high proportion of patients with "missing" race in earlier years, and that race is variably and inconsistently reported between states.…”
Section: Discussionsupporting
confidence: 91%
“…We also observed an increase in the proportion of African Americans dying in the hospital over time, which is consistent with other studies of African American patients with malignancy that have higher shown likelihood of dying in acute care setting [11][12][13]. We would however draw caution in interpreting this finding as inferences on race from the National Inpatient Sample is problematic due to a high proportion of patients with "missing" race in earlier years, and that race is variably and inconsistently reported between states.…”
Section: Discussionsupporting
confidence: 91%
“…After searching almost fourthly-thousand citations, 284 articles were included in our study, of which 147 were manuscripts that directly addressed end-of-life and hospice care, palliative care, as well as advance care planning and directives that include non-Hispanic Blacks. 4 …”
Section: Methodsmentioning
confidence: 99%
“…Our analysis also compared ESLD with other major causes of death and found that although ESLD had the second highest proportion of deaths in hospice, it still substantially trailed malignancy. Based on previous studies in cancer populations, ( 29,44,45 ) we expected and found that patients who died with HCC and non‐HCC malignancy had significantly higher rates of death at hospice and home than other diseases. Death attributed to infection, on the other hand, occurred more often in an inpatient setting, which may be because infections are felt by many to require hospitalization.…”
Section: Discussionmentioning
confidence: 98%
“…These trends have been reflected in other studies, including in patients with Medicare insurance, ( 26 ) chronic lung disease, ( 27 ) dementia, ( 28 ) and malignancy. ( 29 ) Although it is difficult to attribute these changing patterns to a particular intervention or policy change, there has been a progressive move in the United States toward the expansion of hospice services in an effort to decrease health care costs and improve quality of life. ( 30,31 )…”
Section: Discussionmentioning
confidence: 99%